2015
DOI: 10.1007/s40262-015-0309-8
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Safety of Single Intravenous Doses of JNJ-54452840, an Anti-β1-Adrenergic Receptor Antibody Cyclopeptide, in Healthy Male Japanese and Caucasian Participants

Abstract: JNJ-54452840 demonstrated similar pharmacokinetics in both groups. JNJ-54452840 was possibly immunogenic, and two participants reported thromboembolic serious adverse events. The relationship between these events and antibody formation is not known.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…These studies also reconfirmed renal and liver safety. A phase Ib study investigated shorter dosing intervals[ 32 ]–using this unusually short dosing interval regime, two participants with predisposing risk factors (including a factor V Leiden mutation) had thromboembolic adverse events; further detailed analysis including functional tests revealed neither pro-coagulatory nor anti-coagulatory substance-related effects of COR-1 per se . Other experimental antibody-directed strategies consist in their removal from the circulation by specific or non-specific immunoadsorption using either matrix-coupled peptides derived from ß 1 EC2–[ 33 ]or protein A columns[ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…These studies also reconfirmed renal and liver safety. A phase Ib study investigated shorter dosing intervals[ 32 ]–using this unusually short dosing interval regime, two participants with predisposing risk factors (including a factor V Leiden mutation) had thromboembolic adverse events; further detailed analysis including functional tests revealed neither pro-coagulatory nor anti-coagulatory substance-related effects of COR-1 per se . Other experimental antibody-directed strategies consist in their removal from the circulation by specific or non-specific immunoadsorption using either matrix-coupled peptides derived from ß 1 EC2–[ 33 ]or protein A columns[ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immunization of animals with ECL2 of b1AR resulted in deleterious cardiac remodeling reflecting its causative role in DCM. Consistently, an early phase, dose-ranging clinical study using COR-1 indicated tolerability 140 resulting in randomized double-blinded phase II studies 141 (ClinicalTrials.gov.NCT01391507, JNJ-54452840, an anti-b1AR antibody cyclopeptides containing ECL2 shown to reverse anti-b1AR autoantibody-induced myocardial damage in rat 142 ). The randomized study was terminated due to adverse events, but its relationship to autoantibodies could not be determined.…”
Section: Conclusion Challenges and Clinical Implicationsmentioning
confidence: 99%
“…The randomized study was terminated due to adverse events, but its relationship to autoantibodies could not be determined. 141 However, there is increasing appreciation that b1AR autoantibodies may bind to the ECL2 of b1AR regulating receptor function through allosteric modulation without binding to the orthosteric agonist/antagonist site. 10,52,115,122,133 This would allow b1AR autoantibodies to noncanonically modulate agonist and/or antagonist signaling and subsequent cardiac outcomes.…”
Section: Conclusion Challenges and Clinical Implicationsmentioning
confidence: 99%
“…58 One peptide, cyclic peptide (JNJ-54452840), has been investigated in a phase I study in healthy humans and in patients with DCM. 60,61 In a phase II double-blind, parallel-group, controlled trial, patients were randomly assigned to 20, 80, and 160 mg of cyclic peptide, or placebo, given for 6 months.…”
Section: Peptides For Autoantibody Neutralizationmentioning
confidence: 99%